The Use of Bamboo Dancing Technique to Improve the Eleventh Grade Students’ Speaking Achievement - Uli Dwi Setiawan; Bambang Suharjito; Bambang Arya Wija Putra (EFL Education Journal, 2021)
This classroom action research was aimed at improving the eleventh-grade students’ speaking achievement using the bamboo dancing technique and to know the improvement of their participation during the teaching and learning process. The research participants were the XI-IBB 1 students chosen purposively. The students’ speaking scores and observation data were analyzed using descriptive statistics. The results showed that the use of the bamboo dancing technique could improve the students’ speaking achievement and their participation in speaking class. The students who got targeted scores were improved from 70.83% in Meeting 1 to 83.33% in Meeting 2. It was suggested for English teachers to apply the bamboo dancing technique in speaking class.